Repression of MicroRNA-124-3p Alleviates High-Fat Diet–Induced Hepatosteatosis by Targeting Pref-1 - Wang, Guan; Zou, Haibo; Lai, Chunyou; Huang, Xiaolun; Yao, Yutong; Xiang, Guangming (Frontiers in Endocrinology, 2020)
Nonalcoholic fatty liver disease (NAFLD) is the common disease in the liver, which is associated with metabolic syndrome and hepatocellular carcinoma. Accumulated evidence establishes that small non-coding microRNAs (miRNAs) contribute to the initiation and progression of NAFLD. However, the molecular repertoire of miRNA in NAFLD is still largely unknown. Here, using an integrative approach spanning bioinformatic analysis and functional approaches, we demonstrate that miR-124-3p participates in the development of NAFLD by directly targeting preadipocyte factor-1 (Pref-1). In response to high-fat diet (HFD), expression of miR-124-3p was increased in the liver. Inhibition of miR-124-3p expression led to a dramatic reduction of triglyceride contents in hepatocytes, in parallel with decreased inflammatory factors. Mechanistically, miR-124-3p directly controls the transcription of Pref-1, a secretory factor that has been proved to resist metabolic syndrome. Our work identifies a novel molecular axis in hepatosteatosis, and highlights miR-124-3p/Pref-1 as potential targets for clinical interventions of NAFLD.